If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x-1)/15=3(x+3)/9
We move all terms to the left:
9(x-1)/15-(3(x+3)/9)=0
We calculate fractions
9x/()+(-(3(x+3)*15)/()=0
We calculate terms in parentheses: +(-(3(x+3)*15)/(), so:We get rid of parentheses
-(3(x+3)*15)/(
We multiply all the terms by the denominator
-(3(x+3)*15)
We calculate terms in parentheses: -(3(x+3)*15), so:We get rid of parentheses
3(x+3)*15
We multiply parentheses
45x+135
Back to the equation:
-(45x+135)
-45x-135
Back to the equation:
+(-45x-135)
9x/()-45x-135=0
We multiply all the terms by the denominator
9x-45x*()-135*()=0
We add all the numbers together, and all the variables
9x-45x*()=0
| 5-4y-20=0 | | 2/3x+8=1/3x-2 | | 28.65=6g+3.69 | | 5x+6x-4x=35+7 | | -6(-p+80=-6p+12 | | 1v=-29 | | -4(2+6x)=-56 | | 1v=29 | | 7x-2x^2=15 | | 4/5-3x/10=11/15 | | 7x^+9=0 | | 5x-9=2x=3x+3=12 | | 4(-7x+6)=164 | | 2m^2-4=32 | | 13*x=91 | | 2/3p+1/5=4/15 | | 17w-12+3w=18 | | x^2+5x-22=2 | | 36=12n-4n | | x+2=2x-3 | | 3(x-3)=9 | | 2x-4=3^x+1 | | 8x+9x-22=88-5x | | 29=4x=1 | | 7x2+9=0 | | 12x+2x^2=x^2+1 | | (x+3)+(2x+5)+(5x-1)=39 | | 3=1+a/7 | | -3(2n-8)=39 | | 2w+2(3w+5)=5 | | 2w+2=w+1 | | 3*x=99 |